THE PATH FROM INDUSTRIAL INSTITUTE TO NATIONAL RESEARCH UNIVERSITY - A. Kh. Gilmutdinov (Moscow Polytechnic University, 2017)
Interview with the Rector of Kazan National Research Technical University named after A.N. Tupolev - KAI A.Kh. Gilmutdinov.